The global regulator FpLaeB is required for the regulation of growth, development, and virulence in Fusarium pseudograminearum - Wu, Yuxing; Wang, Yajiao; Han, Sen; Li, Qiusheng; Kong, Lingxiao (Frontiers in Plant Science, 2023)
Fusarium pseudograminearum is a soil-borne pathogen that is capable of causing a highly destructive crown disease in wheat. Secondary metabolites (SMs), especially deoxynivalenol (DON), are the primary virulence factors during infection. Here, we characterised the global regulator FpLaeB, an orthologue of LaeB protein function, to regulate the SM in Aspergillus nidulans. Through the utility of the gene targeting approach, we found that the vegetative growth of the FpLaeB deletion mutant was drastically reduced compared to that of the wild type. FpLaeB was also important for conidiation because the FpLaeB deletion mutant formed fewer conidia in induced medium. In addition, the sensitivity of the FpLaeB deletion mutant to the cell wall integrity inhibitor was decreased, while its growth was more severely inhibited by the cell membrane inhibitor sodium dodecyl sulfate (SDS) than that of the wild type. More importantly, the virulence was decreased when the FpLaeB deletion mutant was inoculated onto the wheat stem base or head. Through genome-wide gene expression profiling, FpLaeB was found to regulate several processes related to the above phenotypes such as the carbohydrate metabolic process, which is an integral and intrinsic component of membranes, especially SMs. Furthermore, the generation of DON was impaired in the FpLaeB deletion mutant via ultraperformance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) assay. These results showed that FpLaeB plays an important role in the growth, development, and maintenance of the cell wall, and in membrane integrity. More importantly, FpLaeB is required for SMs and full virulence in F. pseudograminearum.